Pathological features and clinical outcomes of breast cancer according to levels of oestrogen receptor expression. Issue 4 (1st August 2014) - Zhang, Zhang; Wang, Jianmin; Skinner, Kristin A; Shayne, Michelle; Hajdu, Steven I; Bu, Hong; Hicks, David G; Tang, Ping
Abstract : Aims: Historically, nuclear staining of ≥10% of invasive tumour cells has been used for oestrogen receptor (ER) positivity. In 2010, ASCO/CAP guidelines recommended the cut‐off value be changed to nuclear staining of ≥1%. This study will analyse the relationships between levels of ER expression and clinicopathological features and clinical outcomes, with an emphasis on the ER 1–10% subgroup. Methods and results: We analysed clinicopathological features in five subgroups based on ER expression levels in 1700 consecutive invasive breast cancer patients diagnosed and treated at our institution between 2000 and 2011. Of the cases, 24% had ER expression <1%, 2% were ER 1–10%, 5% were 11–50%, 5% were 51–70% and 64% were 71–100%. We observed four subgroups of patient cohorts (ER <1%, 1–10%, 11–70% and 71–100%) that were unique in Nottingham grade, nuclear grade, progesterone receptor expression and disease‐free survival. Of the 341 patients with follow‐up data, we found no significant differences in pathological features between patients in the ER 11–50% and ER 51–70% subgroups. Conclusion: These data support the important role of ER in breast cancer, and the importance of accurate testing and quantitative reporting for ER. Tumours with ER 1–10% are not common, and further studies are needed to understand more clearly this subgroup of breast cancer.